2020
DOI: 10.1097/dcr.0000000000001626
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as an Alternative Radiosensitizing Agent to 5-Fluorouracil During Neoadjuvant Treatment for Rectal Cancer

Abstract: BACKGROUND: Neoadjuvant chemoradiation for locally advanced rectal cancer combining 5-fluorouracil with radiation increases tumor regression compared with radiation alone. However, it occurs at the cost of significant treatment-related toxicity. Patients with rectal cancer using metformin have been associated with improved response to radiotherapy. OBJECTIVE: The purpose of this study was to evaluate the radiosensitizing effects of metformin in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…However, research into the methylation regulation of TGFBI in RC has not been reported. Pathway analysis also revealed that these MeDEGs were enriched in the PI3K-Akt signaling pathway, which was involved in multiple types of malignancies [46,47] , including RC [48] . In the current study, we identi ed many aberrantly methylated and expressed genes participating in the PI3K-Akt signaling pathway, which could provide a foundation for experimental research in RC.…”
Section: Discussionmentioning
confidence: 95%
“…However, research into the methylation regulation of TGFBI in RC has not been reported. Pathway analysis also revealed that these MeDEGs were enriched in the PI3K-Akt signaling pathway, which was involved in multiple types of malignancies [46,47] , including RC [48] . In the current study, we identi ed many aberrantly methylated and expressed genes participating in the PI3K-Akt signaling pathway, which could provide a foundation for experimental research in RC.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have shown that metformin inhibits cell proliferation and increases apoptosis in various cancer cells [ 34 , 35 ]. Metformin could be as radiosensitizer that improves the sensitivity of several cancer cells to irradiation therapy [ 36 , 37 ]. Moreover, recent clinical data showed that colorectal carcinoma (CRC) patients treated with metformin due to coexisting diabetes developed fewer distant metastases and survived longer compared to those not treated with metformin [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibition of cancer cell proliferation, metformin might improve radiation response by decreasing tumor hypoxia-mediated radiation resistance [13]. There is preclinical evidence that metformin serves as a radiosensitizing agentand improves radiation treatment response in various cancer cell lines including colorectal cancer [13,23]. Metformin has thus been proposed as a novel radiation modifier [22,24].…”
Section: Discussionmentioning
confidence: 99%